Evaluation of The Implementation of The Daily Financial E-Report System at The Shopee Express Shipping Office - Nining Susanti; Mahyudin; Minasari Nasution (Journal of Finance Integration and Business Independence, 2025)
This research arises from the growing need for a fast, accurate, and adaptive financial reporting system in line with the rapid digital transformation occurring in the expedition service industry. As a logistics provider, Shopee Express requires an information system capable of enhancing operational efficiency and strengthening accountability. This study focuses on evaluating the implementation of a daily e-financial reporting system at the Shopee Express operational unit in Bandar Perdagangan to determine its effectiveness and the challenges faced during its adoption. A qualitative-descriptive case study method was used, with data collected through triangulation, including user interviews, direct observation of reporting procedures, and documentation review. Analysis employed the PIECES framework (Performance, Information, Economy, Control, Efficiency, Service) to identify both strengths and system limitations. Findings show that the daily e-financial reporting system has significantly improved reporting speed, data accuracy, and internal control mechanisms. However, some issues remain, such as inadequate user training and limited system integration, which may hinder further optimization. Overall, users expressed positive acceptance due to the system’s ease of use, intuitive interface, and reliable information output. This study concludes that the daily e-financial reporting system is an essential asset that supports Shopee Express’s operational performance. Recommendations include enhancing training programs and adopting scalable cloud-based technologies